2021
DOI: 10.17645/si.v9i3.4125
|View full text |Cite
|
Sign up to set email alerts
|

Digital Teaching, Inclusion and Students’ Needs: Student Perspectives on Participation and Access in Higher Education

Abstract: In this article we discuss the contribution of digitalisation for equal participation in higher education. Its potential is often postulated, but accessibility is seldom examined in this context. Despite the challenges and difficulties created in the summer term of 2020, this semester has provided a great opportunity to collect data on digital teaching, as face‐to‐face teaching needed to be transformed into digital teaching. Based on two surveys conducted in the summer of 2020, current practices and students’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…Different levels of progress are also apparent in moving beyond “ERTL”, with initial progress – for instance creating well-packaged but unexciting learning packages, or well-produced online lectures – not always being followed by the development of more diverse approaches geared to the needs of work-based learners. Attention is also needed to the choice of hardware and digital platforms, ensuring that technology is suitable for work-based applications as well as delivery-based online learning, fully accessible from home and work as well as from the institution, and supportive of accessibility principles such as universal design (Nottingham, 2021; Wilkens et al. , 2021).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Different levels of progress are also apparent in moving beyond “ERTL”, with initial progress – for instance creating well-packaged but unexciting learning packages, or well-produced online lectures – not always being followed by the development of more diverse approaches geared to the needs of work-based learners. Attention is also needed to the choice of hardware and digital platforms, ensuring that technology is suitable for work-based applications as well as delivery-based online learning, fully accessible from home and work as well as from the institution, and supportive of accessibility principles such as universal design (Nottingham, 2021; Wilkens et al. , 2021).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Research has found that institutions pose a challenge to academics by not providing digital devices such as computers on time; sometimes they are not provided at all. Wilkens et al (2021) maintain that HEIs have the responsibility to provide accessible ICT. Often what staff do receive are old computers and other ICT tools.…”
Section: Digital Challenges In Open Distance Educationmentioning
confidence: 99%
“…The question arises as to what attitudes and competences these lecturers hold. -beschulung erkannt worden (Rapanta, Botturi, Goodyear, Guàrdia & Koole, 2021 ;Wilkens, Haage, Lüttmann & Bühler, 2021). Dennoch bleibt unklar, inwiefern die Erfahrungen mit digitalmediatisiertem Lehren und Lernen zu einer Neubewertung der Relevanz und einem Verständnis für die komplexe Verschränkung von Medienbildung und Inklusion in den einzelnen Fächern führt.…”
unclassified
“…. Es finden sich vielmehr Analysen aus fachunabhängigen sowie aus sonderpädagogischen Perspektiven(Wilkens et al, 2021). Die Lücke hinsichtlich Germanistik und Englisch klafft angesichts der Zentralität der Mediatisierung bzw.…”
unclassified